Al2O3 Diffusion Barrier: In‐Situ Observation of the Formation of NiSi/Ni2Si Heterojunction in SiGe Nanowire with Al2O3 Diffusion Barrier Layer (Adv. Mater. Interfaces 14/2021). Issue 14 (23rd July 2021) - Lee, Yu‐Chuan; Lyu, Lian‐Ming; Lu, Ming‐Yen
Abstract : In article number 2100422, Yu‐Chuan Lee, Lian‐Ming Lyu, and Ming‐Yen Lu demonstrate the manipulation of the phases of Ni silicides when Ni diffuses into SiGe nanowire (NW) with the introduction of Al2 O3 diffusion barrier. Since the diffusion barrier is very thin (≈5 nm), Ni atoms can pass through the barrier and form the NiSi/Ni2 Si heterojunction with SiGe NW. This study provides the insights for fabrication of semiconducting devices.